Strategi Kelayakan Pendirian Usaha Eco Briket yang Memanfaatkan Limbah Ampas Kopi - Ema Marliana; Vioga Apriza Pranadewangga; Nisrina Septiani Nugraheni; Tri Pidianto; Darena Fauzi; Setya Indah Isnawati (Pusat Riset dan Inovasi Nasional, 2024)
Eco Briquette is a business engaged in the trade sector that sells charcoal briquettes from coffee grounds waste, which is planned to be marketed to restaurants and MSMEs that use charcoal as a cooking medium for their products. Eco Briquette seeks to introduce this coffee charcoal briquette to be used in restaurants, MSMEs and even supermarkets in Semarang Regency and its surroundings. This is not done without reason, considering the advantages of this coffee grounds charcoal briquette are very many compared to the use of ordinary charcoal. The advantage of using Eco Briquette is its usability and uses coffee grounds waste materials that are rarely used in other briquettes. Unlike wood charcoal or other fuels that are easily used up or burn quickly, coffee grounds charcoal briquettes have a long useful life because they do not run out quickly when burned. In the process of burning charcoal briquettes, there is no flying powder and also the smoke produced by charcoal briquettes is not as much as ordinary charcoal, this can also reduce smoke pollution in Semarang Regency, especially in the Ungaran industrial area. The use of coffee grounds charcoal briquettes is also considered safer than regular charcoal, because it has a slow burning rate.